Parental Support for the Training Motivation of Beginner Fencing Athletes - Titik Setyorini; Dwi Gansar Santi Wijayanti (Journal of Physical Education Health and Sport, 2025)
This study aims to determine the level of parental support for the training motivation of beginner fencing athletes in Kendal Regency. The method used is a survey with a descriptive quantitative approach. The sample consisted of 45 beginner fencing athletes selected through quota sampling. Data were collected using a Likert scale questionnaire that had been tested for validity and reliability. The results showed that parental support was in the moderate category with an average score of 2.54 or 56%, while athlete training motivation was in the good category with an average score of 2.72 or 60%. These findings indicate that although parental support is not yet optimal, athletes still show strong enthusiasm and commitment in their training. This study highlights the importance of parental involvement, particularly in the form of emotional and instrumental support, in enhancing motivation and athletic performance among beginners. It is recommended that parents become more actively involved in their children’s training activities and maintain regular communication with coaches.